Indications and Complication of Laparoscopic Cholecystectomy at a Tertiary Care Setting in Sindh Province: A Cross Sectional Survey - Sasui Wadho, Pooja Kumari, Nargis Shaikh, Nadia Bhatti, Abdul Ghani Shaikh, Mohammad Ali Naper (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study was aimed to-evaluate the indications and-complications-of the laparoscopic cholecystectomy at a tertiary care setting in sindh province. Background: The-hepato-biliary-system is affected by a wide range of illnesses known as gall bladder diseases, each of which has a unique clinical presentation and degree of morbidity. The majority of adult populations in Western nations are affected by cholelithiasis, which affects 5% to 25% of the adult population. Initially, people from developing nations had little access to the advantages of laparoscopic cholecystectomy. Materials and Methods: A cross sectional study was carried out at the surgical dept Chandka Medical College Hospital Larkana for a period of 6 months in 2020 which included patients who went through laparoscopic cholecystectomy were included in the study, however, the patients having a history of previous abdominal surgery, hepatobiliary carcinoma , challenges ejection fraction, patients with coagulopathies and those reactive for HbsAg or HCV antibodies were excluded from the study. Results: The mean age of the subjects was 43.8± 9.67 years. There were 93.7% of study participants were females, 18.6% were diabetic and 26.5%) were hypertensive. 41.81% patients were aged between 30 to 40 years. The indications for the cholecystectomy included Symptomatic cholelithiasis for 148 (83.62%) cases, acute cholecystitis for 24(13.56%) cases and gall bladder polyp for 5 (2.82%) cases. There were 11 (6.21%) cases which needed to be converted to open cholecystectomy. Bile leaking was reported in 8 (4.52%) cases and injury to liver/intestine were reported for 3 (1.69%) cases. Conclusion: In a setting of a developing country, -laparoscopic-cholecystectomy-looks to be a safe and-effective treatment with few complications. Keywords: Laparoscopic cholecystectomy, Indications, Complications, cholelithiasis.